"Mommy and Me": raising implicit followership theories. Issue 2 (5th January 2021) - Hoption, Colette; Han, Jiashan Mary
Abstract : Purpose: The purpose of this paper is to examine the antecedents to implicit followership theories (IFTs) and make recommendations for developing positive IFTs. Female transformational parenting is highlighted, showing that although followership is typically associated with one's role in an organization, its development is not relegated to that context. Accordingly, this paper encourages transformational-parenting training and features activities for current leader-training programs to enlighten trainees about their IFTs. Design/methodology/approach: Through one online and one paper survey, participants self-defined "follower, " rated their female primary caregivers' transformational leadership during adolescence, reported their IFTs and provided demographic information. Findings: Qualitative and quantitative data analyses found that the degree to which female primary caregivers demonstrated transformational leadership related to children's positive IFTs and positive definitions about followers in young adulthood. Research limitations/implications: Future research should test female caregivers' influence on IFTs at more advanced stages of one's career, examine their influence over participants' followership behavior and incorporate external ratings of leadership and followership. Practical implications: Recommendations for embedding IFTs into transformational-leadership-training programs are provided, falling into the categories of feedback, reflection/introspection and mentoring/coaching. In the spirit of contemporary approaches to leadership, recommendations require trainees to recognize their biases/knowledge of followers and followership and use that knowledge to facilitate collaboration between leaders and followers. Originality/value: Findings spotlight female leadership, an often-overlooked source of power in organizations, and go beyond leader/follower dichotomies by insisting on IFTs awareness and development for both parties.